Label-free assessment of intestinal inflammation in patients with ulcerative colitis using digital holographic microscopy - Bokemeyer, A.; Buskermolen, J.; Ketelhut, S.; Tepasse, P. R.; Vollenberg, R.; Trebicka, J.; Schmidt, H. H.; Vieth, Michael; Bettenworth, D.; Kemper, Björn (Digital Holography and Three-Dimensional Imaging, DH 2024 in Proceedings Optica Digital Holography and Three-Dimensional Imaging 2024, DH, 2024)
We evaluated the application of quantitative phase imaging (QPI) with digital holographic microscopy (DHM) for the assessment of histopathological inflammation in patients with ulcerative colitis (UC).
CRIS-Team Scopus Importer:2024-10-04